An oocyte meiotic midbody cap is required for developmental competence in mice - Gyu Ik Jung; Daniela Londoño-Vásquez; Sungjin Park; Ahna R. Skop; Ahmed Z. Balboula; Karen Schindler (Nature Communications, 2023)
Abstract Embryo development depends upon maternally derived materials. Mammalian oocytes undergo extreme asymmetric cytokinesis events, producing one large egg and two small polar bodies. During cytokinesis in somatic cells, the midbody and subsequent assembly of the midbody remnant, a signaling organelle containing RNAs, transcription factors and translation machinery, is thought to influence cellular function or fate. The role of the midbody and midbody remnant in gametes, in particular, oocytes, remains unclear. Here, we examined the formation and function of meiotic midbodies (mMB) and mMB remnants using mouse oocytes and demonstrate that mMBs have a specialized cap structure that is orientated toward polar bodies. We show that that mMBs are translationally active, and that mMB caps are required to retain nascent proteins in eggs. We propose that this specialized mMB cap maintains genetic factors in eggs allowing for full developmental competency.